농업용수 수리권 평가 및 개선 방안(Ⅰ) : 법 및 제도 - 김홍상 (한국농촌경제연구원, 2006)
Recently there are growing concerns on reducing agricultural water use and utilizing agricultural water for other purposes. These demands came from several sources such as the growing non-agricultural water demands and the difficulty of constructing new dams. This study was initiated to provide a theoretical foundation on agricultural water rights from the current nationwide discussions of modifying the structure of water use rights. Although the agricultural water use consists more than half of the whole water use in the country, few studies focus on agricultural water rights problems due to customary agricultural water use and its lack of a legal definition. Therefore, this study suggests how to improve laws and institutions related with agricultural water rights by analyzing laws and institutions of agricultural water use, current institutional structure of water use, and water use rights of foreign countries. This study analyzes and discusses the following topics with case studies: current agricultural water rights problems, the utilization and management of agricultural water rights, water use rights conflicts between agriculture and other sectors, water use conflicts within agriculture, and water user rights for trade. In the study, we also discussed and analyzed legal and institutional problems concerning the water use, such as conflicts between customary and authorized water use rights, unclear definitions on the range of vested water use rights, unclearly identified holders of agricultural water rights, and inadequately secured agricultural water use rights. In addition, we also reviewed similar cases in Australia, the U.S., and France, which are aggressively reforming water use rights, and Japan, whose system resembles that of Korea. The results of case study suggest a possible option for introducing tradable water use permits, fixing related laws, and protecting agricultural water use rights. Finally, this study suggests how to improve legal and institutional settings for agricultural water use rights. Especially, this study accentuates several things to consider. These include minimizing conflicts over water use rights, agricultural water rights as the first priority among other water uses, the efficient water-saving of agricultural water use, direction of long-term water management, and issues on introducing tradable water permits. Researchers: Hong-Sang Kim(hskim@krei.re.kr)Joo-Nyung Heo(knuhjn@krei.re.kr)